1995
DOI: 10.1111/j.1600-0609.1995.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of a histologic classification system applied in bone marrow biopsies from patients with multiple myeloma: A histopathological evaluation of biopsies from 153 untreated patients*

Abstract: A total of 153 diagnostic bone marrow biopsies from patients with advanced stages of multiple myeloma corresponding to stages II and III according to the Durie/Salmon classification were evaluated prior to any treatment in a prospective therapy trial of the German Myeloma Treatment Group. Histologic sections were analyzed according to a pre‐defined system of criteria microscopically by 2 observers, determining three criteria: 1) grading by histopathology, regarding the cytologic differentiation of neoplastic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 18 publications
2
19
0
5
Order By: Relevance
“…The criteria put forward by the German myeloma task force was used by us to type the plasma cell morphology into well differentiated, intermediately differentiated or poorly differentiated plasma cells. [7] Mitosis was counted in 20 high power fields showing plasma cell infiltration in the biopsy and was categorized as 0-1/ 10 hpf, 2-5/10 hpf and >5/10 hpf. Fibrosis was graded between grade 0 and 3 as per the European Consensus method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The criteria put forward by the German myeloma task force was used by us to type the plasma cell morphology into well differentiated, intermediately differentiated or poorly differentiated plasma cells. [7] Mitosis was counted in 20 high power fields showing plasma cell infiltration in the biopsy and was categorized as 0-1/ 10 hpf, 2-5/10 hpf and >5/10 hpf. Fibrosis was graded between grade 0 and 3 as per the European Consensus method.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Several clinical, laboratory and histological/cytological variables help us in determining the prognosis of the disease. [1,[3][4][5][6][7] The first histological classification and staging of multiple myeloma, based on the bone marrow trephine biopsy, was put forward by Bartl et al in 1987. [3] The Durie and Salmon clinical staging system, proposed in 1977, [8] is still being used today, though it has been replaced by the ISS staging at many places.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of clinical variables were particularly analyzed: age, gender, clinical stage, presence and extent of bone lesions, serum immunoglobulins, serum and urine immunoelectrophoresis, albumin, C-reactive protein, b 2 -microglobulin, calcium, creatinine, 24-h proteinuria, hemoglobin concentration, and platelet count. Classification of the histological grade of plasma cell differentiation was done according to the model proposed by Sailer et al [12] and was defined as low, intermediate, and high-grade plasma cell malignancy. Classification of the histological stage (i.e., the extent of bone marrow infiltration) was done according to the model proposed by Bartl et al [13] as follows: stage I or lowgrade bone marrow infiltration (plasma cells \20% of all nucleated cells, ANC), stage II or intermediate infiltration (plasma cells 20-50% ANC), and stage III or high-grade bone marrow infiltration (plasma cells [50% ANC).…”
Section: Patientsmentioning
confidence: 99%
“…The proliferative rate with MIB1 labeling index was extremely high, suggesting morphologic features of PBL rather than those of plasmablastic EP because Vega et al (8) reported that PBL was characterized by a monotonous proliferation of plasmablasts and/or immunoblasts, with rare or no obvious plasmacytic cells. However, in H&E-stained sections, plasmablastic features were defined as equal to or greater than 30% of blasts (16). In fact, plasmacytic cells were frequently seen in plasmablastic MM (8).…”
Section: Discussionmentioning
confidence: 99%